2021
DOI: 10.2478/ijame-2021-0044
|View full text |Cite
|
Sign up to set email alerts
|

Three-Bladed Horizontal Axis Water Turbine Simulations with Free Surface Effects

Abstract: The water level above a hydrokinetic turbine is likely to vary throughout the season and even along the day. In this work, the influence of the free surface on the performance of a three bladed horizontal-axis turbine is explored by means of a three-dimensional, transient, two-phase flow computational model implemented in the commercial CFD software ANSYS Fluent 19.0. The k – ω SST Transition turbulence model coupled with the Volume of Fluid (VOF) method is used to track the air-water interface. The rotor diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, Rodríguez et al, showed that ANSYS-Fluent software, which is a commercially available CFD tool, use VOF model to accurately monitor the interface between air and water. Additionally, the unstable Reynolds-averaged Navier-Stokes (URANS) SST k-ω and Transition SST turbulence models are utilised to calculate the unsteady flow field [40]. Rubio-Clemente et al, also provided that the numerical simulation accuracy was improved by utilizing ANSYS Fluent software, which incorporated a 6-DoF user-defined function and URANS equations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, Rodríguez et al, showed that ANSYS-Fluent software, which is a commercially available CFD tool, use VOF model to accurately monitor the interface between air and water. Additionally, the unstable Reynolds-averaged Navier-Stokes (URANS) SST k-ω and Transition SST turbulence models are utilised to calculate the unsteady flow field [40]. Rubio-Clemente et al, also provided that the numerical simulation accuracy was improved by utilizing ANSYS Fluent software, which incorporated a 6-DoF user-defined function and URANS equations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rodriguez et al [23] performed two-phase flow simulations of the HAHT rotor described in Bahaj et al [17], for two blade tip immersions and three TSRs. The computational approach incorporated a transition four-equation turbulence model, the Volume of Fluid (VOF) method for interface tracking, and the sliding-mesh technique to account for blade rotation.…”
Section: Introductionmentioning
confidence: 99%